Molecular Mechanism of the β-Lactamase Mediated β-Lactam Antibiotic Resistance of Pseudomonas aeruginosa Isolated From a Chinese Teaching Hospital - Lin, Hailong; Feng, Chunlin; Zhu, Tingting; Li, Anqi; Liu, Shuang; Zhang, Lei; Li, Qiaoling; Zhang, Xueya; Lin, Li; Lu, Junwan; Lin, Xi; Li, Kewei; et al. (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa can cause infections in the blood, lungs (pneumonia), or other parts of the body after surgery. To investigate the molecular characteristics of β-lactam antibiotic resistance of Pseudomonas aeruginosa isolated from a hospital population between 2015 and 2017, in this study, the antimicrobial susceptibility and the resistance gene profile of the bacteria were determined. The Pulsed-ﬁeld gel electrophoresis (PFGE) was used to characterize the clonal relatedness and sequencing and comparative genomic analysis were performed to analyze the structure of the resistance gene-related sequences. As a result, of the 260 P. aeruginosa strains analyzed, the resistance rates for 6 β-lactam antibiotics ranged from 4.6% to 9.6%. A total of 7 genotypes of 44 β-lactamase genes were identified in 23 isolates (8.9%, 23/260). Four transconjugants from different donors carrying blaCARB-3 exhibited a phenotype of reduced susceptibility to piperacillin-tazobactam, ceftazidime and cefepime, and 2 transconjugants harbouring blaIMP-45 exhibited a phenotype of reduced susceptibility to carbapenems. blaCARB positive isolates (n =12) presented six PFGE patterns, designated groups A to F. Two bla genes (blaIMP-45 and blaOXA-1) in PA1609 related to a class 1 integron (intI1-blaIMP-45-blaOXA-1-aac(6’)-Ib7-catB3-qacE∆1-sul1) were encoded on a plasmid (pPA1609-475), while the blaCARB-3 gene of PA1616 also related to a class 1 integron was located on the chromosome. The results suggest that β-lactam antibiotic resistance and clonal dissemination exist in this hospital population. It indicates the necessity for molecular surveillance in tracking β-lactamase-producing strains and emphasizes the need for epidemiological monitoring.